Nerve growth factor (NGF)-TrkA axis in head and neck squamous cell carcinoma triggers EMT and confers resistance to the EGFR inhibitor erlotinib. (1st March 2020) - Lin, Chengzhong; Ren, Zhenhu; Yang, Xi; Yang, Rong; Chen, Yiming; Liu, Zheqi; Dai, Zhenlin; Zhang, Yu; He, Youya; Zhang, Chunye; Wang, Xu; Cao, Wei; et al.
Abstract: Understanding the molecular mechanisms regulating tumor dissemination and therapeutic resistance is of central importance for effective cancer therapies. Here, we report that nerve growth factor (NGF) and its receptor TrkA facilitate epithelial-mesenchymal transition (EMT) and EGFR inhibitor resistance via STAT3 activation in head and neck squamous cell carcinoma (HNSCC). Both NGF and TrkA expression were elevated in HNSCC, indicating poor clinical outcomes. NGF was highly expressed in cancer cells and nerves in perineural niche, whereas TrkA expression was higher in cancer cells with perineural invasion. The NGF/TrkA axis could promote HNSCC cell dissemination and trigger EMT via STAT3 activation. Moreover, we discovered that the NGF/TrkA axis conferred resistance to the EGFR inhibitor erlotinib via EMT processes in HNSCC cells. Blocking TrkA signaling markedly reversed EMT and sensitized HNSCC cells to erlotinib in both in vitro and in vivo models. Overall, our results demonstrate novel evidence that the paracrine NGF/TrkA axis favors EMT and confers EGFR-targeted therapeutic resistance in HNSCC. Highlights: Paracrine NGF/TrkA axis triggers EMT in HNSCC perineural niche. NGF/TrkA axis confers resistance to the EGFR kinase inhibitor erlotinib via EMT and STAT3 signaling in HNSCC cells. TrkA could be a novel therapeutic target for overcoming EGFR-targeted therapeutic resistance in HNSCC patients.